Business Communication Course - Evan Moreno; Mada Aditia Wardhana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
Business communication courses play a critical role in preparing business school graduates for the demands of global communication. This study aims to analyze the comparison between the integration of research-based best practices and administrative procedural guidelines in the design of Business Communication course curricula, as well as to evaluate the contribution of integrating intercultural awareness and self-efficacy in meeting international business communication skill requirements from the employer’s perspective. The study was conducted through a systematic review of academic literature using thematic analysis methods. The findings reveal that evidence-based approaches, such as the implementation of Constructive Alignment and student engagement as co-creators, produce more transformative curricula that focus on the development of authentic competencies, compared to administrative approaches that tend to be limited to procedural compliance. Furthermore, the integration of intercultural awareness that fosters transcultural understanding, together with the development of self-efficacy through techniques such as personal mastery, synergistically equips students with a global mindset and confidence that align directly with employers’ expectations of graduates capable of communicating effectively in international business contexts. Consequently, evidence-based and holistic curriculum design is key to bridging the gap between education and professional practice.